PENGARUH KUALITAS LAYANAN, KENIKMATAN BELANJA, DAN DISKON HARGA TERHADAP PEMBELIAN IMPULSIF - Fadila Suri Astuti; Wiyadi Wiyadi (Value : Jurnal Manajemen dan Akuntansi, 2023)
Companies are required to fulfill all desires according to what consumers need, as a result, a company must continue to innovate to build consumer loyalty to a product offered by the company. The research that has been carried out certainly has the aim of analyzing the influence of independent variables including service quality, shopping enjoyment, and price discounts on the dependent variable, namely impulsive purchases at the Shopee market place. The population of this research or research includes S1 students at the Muhammadiyah University of Surakarta. Furthermore, a sample of 115 respondents was taken using the formula, namely Slovin. The method when collecting data is by using a questionnaire that has been distributed via WhatsApp and Instagram social media. Then the sampling technique chosen by the researcher was non-probability sampling with the incidental sampling method processed using the IBM SPSS 25 application. Testing the data instrument used validity and reliability tests. Furthermore, the data analysis used is multiple linear regression analysis. The results of this study prove that service quality, shopping enjoyment, and price discounts have a positive and significant effect on impulse purchases. Keywords: Service Quality, Shopping Enjoyment, Price Discount